Da Teoria à Prática: Desafios e Aprendizagens no Estágio em Ensino de Educação Física - Duarte Almeida Guimarães Costa Silva (2024)
The school placement carried out as part of the Master's Degree in Teaching Physical Education in Primary and Secondary Education, at the Faculty of Sport of the University of Porto, was intended to conclude the training with a Master's degree and to be a first contact with the reality of being a teacher. This internship report portrays all the learning, experiences and challenges I went through during these nine months of teaching practice. Throughout this school placement, I understood all the difficulties involved in being a Physical Education teacher, the detailed associated with the preparation of each lesson, the relationship with the students and the reflective process inherent in the profession. The purpose of writing this document is to describe all the experiences I had during this internship, which took place at the School in the district of Porto. During the school year, I was in charge of the 12th grade class, in the subjects of Team Sports and Leisure Activities. I will then present all the differences I encountered and associated with teaching a theoretical subject and a practical subject. This document also includes a research project. This is based on the study of the influence of sport on students' attitudes and values and the way they frame them in class. Therefore, the aim of this document is to demonstrate my journey and my learning process in becoming a teacher by showing all the tasks I've been involved in and the dedicationI've put into this phase of my journey in order to improve and become the best teacher I can be. In addition, this report also aims to demonstrate the importance that sports practice can have in the lives of 12th grade students, both in terms of thedevelopment and acquisition of attitudes and values, as well as the benefits and advantages it can bring.